Increasing the Productivity of Waqf Land in Indonesia: Issues and Solutions - Arief, Suyoto; Mahfudz, Akhmad Affandi; Fasa, Muhammad Iqbal; Wibisono, Vina Fithriana; Afifah, Amatulloh Nur (ZISWAF, 2023)
Waqf is one of the resources with enormous potential for Islamic economic growth in Indonesia. This is evident in the existence of waqf land reaching 420.000 hectares which has not been fully optimized, leading to the classification of the land as traditional work. The phenomenon showed the need to manage waqf land properly to ensure more productivity. Therefore, this study aimed to explore the appropriate strategy to manage waqf land in Indonesia with a focus on the problems and solutions. This was achieved using a qualitative method through the application of the Analytic Network Process (ANP). Primary data were collected through the assessment of the problems by the respondents and subsequently categorized using a numerical scale. The results showed that the six problems to be prioritized in ensuring productivity in waqf lands include human resources, literacy comprehension, management system, socio-cultural, legal certification, and government policy. Meanwhile, the solutions required to be prioritized in solving these problems include increasing the supervision term for waqf land, socialization within the community, nadzir competence, reducing the cost of certification, minimizing operational costs, and improving the standard of recruitment into nadzir. The results are expected to serve as an alternative approach to elevating the quality of management as well as addressing human resource, institutional, and regulatory challenges within the Indonesian waqf system.